2012
DOI: 10.1089/ars.2011.4404
|View full text |Cite
|
Sign up to set email alerts
|

Peroxiredoxins in Parasites

Abstract: The new nomenclature should stimulate the crossfertilization of ideas among parasitologists and with the broader redox research community. The diverse parasite developmental stages and host environments present complex systems in which to explore the variety of roles played by Prxs, with a view toward parlaying what is learned into novel therapies and vaccines that are urgently needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
64
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(74 citation statements)
references
References 271 publications
3
64
0
2
Order By: Relevance
“…21 Thus, to assess the "sensitivity" of these plasmodial enzymes, studies are needed that define the rate of hyperoxidation as a function of H 2 O 2 concentration. As noted in our review, 3 as of yet no Plasmodial Prx is known to be sensitive, consistent with none of these organisms having the sulfiredoxin enzyme that has the physiological role of reactivating hyperoxidized Prxs.…”
Section: Features Of Prx1 Family Disulfide Bonds Are Not Unusualsupporting
confidence: 81%
See 2 more Smart Citations
“…21 Thus, to assess the "sensitivity" of these plasmodial enzymes, studies are needed that define the rate of hyperoxidation as a function of H 2 O 2 concentration. As noted in our review, 3 as of yet no Plasmodial Prx is known to be sensitive, consistent with none of these organisms having the sulfiredoxin enzyme that has the physiological role of reactivating hyperoxidized Prxs.…”
Section: Features Of Prx1 Family Disulfide Bonds Are Not Unusualsupporting
confidence: 81%
“…According to a recent survey we completed, 3 all parasites that cause a significant burden of disease feature Prxs among their countermeasures against the host immune system, and these enzymes have been considered as potential targets for drug development. 4 As part of our survey, we found that the naming of many Prxs in various parasites was highly inconsistent, making comparisons difficult.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These enzymes exist in almost all organisms (Chae et al, 1994;Robinson et al, 2010), and appear to be abundant in parasitic nematodes, with the ability to deoxidize H 2 O 2 into water in a system comprised by thioredoxin, thioredoxin reductase and NADPH (Chandrashekar et al, 2000;Henkle-Dührsen and Kampkötter, 2001). Although helminth TPXs have been extensively characterized (Gretes et al, 2012), limited information is available for Trichinella.…”
Section: Introductionmentioning
confidence: 99%
“…Leishmania infantum, an intracellular protozoan parasite with a digenetic life cycle (i.e., it shuttles between two hosts, insects and mammals), encodes several 2-Cys-Prxs (10)(11)(12), one of which is the mitochondrial homolog called mitochondrial tryparedoxin-peroxidase mTXNPx (13). We showed that mTXNPxdeficient promastigotes (i.e., the insect form) are significantly more sensitive to a temperature shift from 25°C to 37°C than promastigotes harboring functional mTXNPx (13).…”
mentioning
confidence: 99%